1980
DOI: 10.1002/pssb.2220980243
|View full text |Cite
|
Sign up to set email alerts
|

Additional Waves and Polariton Dispersion in CdS Crystals

Abstract: A study of additional waves in the exciton region of CdS crystals is reported. Transmittivity and reflectivity of thin crystals is measured showing a structure due to the Fabry‐Perot interference and the interference of additional waves. This structure is a direct reflection of the polariton dispersion law. Using the formulas for a spatially dispersive platelet and Pekar's additional boundary conditions the theoretical reflectivity curves are obtained numerically reproducing the essential experimental results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…exciton-polaritons. 20,60,84,85,87,[109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128] The new quasi-particles are represented in the energy vs. wave-vector dispersion by the lower and upper polariton branch, respectively. There is a similarity with the bonding and anti-bonding molecular levels that arise from the interaction of resonant orbitals of two atoms.…”
Section: Exciton-polaritons In Macroscopic Crystals Of Znomentioning
confidence: 99%
“…exciton-polaritons. 20,60,84,85,87,[109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128] The new quasi-particles are represented in the energy vs. wave-vector dispersion by the lower and upper polariton branch, respectively. There is a similarity with the bonding and anti-bonding molecular levels that arise from the interaction of resonant orbitals of two atoms.…”
Section: Exciton-polaritons In Macroscopic Crystals Of Znomentioning
confidence: 99%
“…Dispersion curves of the transverse exciton (dotted curve) and the polariton (thin solid curves) were derived using parameters of the exciton translational mass M7-=2.3mo and the LT splitting EL ~"£ , r == 5.7 meV [11]. The open circles correspond to the quantized exciton states of CdS, CdSe [12,13], and CuCl [14]. In their reflection and transmission spectra, both even and odd n states were observed in the energy region of E < EL, and double spacing appeared only when E > E^.…”
Section: Optical Selection Rule and Oscillator Strength Of Confined Ementioning
confidence: 99%
“…At the same time, the data presented by different authors differ very much in the near band edge region were the lasing modes are observed. At these short wavelengths the measurements are markedly affected by strong absorption, exciton resonances and the interference of additional waves 19,20 resulting in an interference fringe structure significantly different from the classical Fabry-Pérot one.…”
Section: Refractive Index Dispersion Deduced From Lasing Modes In Znomentioning
confidence: 97%